AKTIVITAS ANTIOKSIDAN DARI EKSTRAK DAUN TELANG (Clitoria ternatea L) - Semi; Elly Rustanti; Siti Mudrikatin (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2022)
Telang (Clitoria ternatea) has long been used as a traditional medicine for the cure of various diseases. Commonly used parts of Clitoria ternatea are flowers and leaves. The leaves of telang flowers contain flavonoids, flavanol glycosides, kaempferol glycosides, quercetin glycosides and glycoside mirisetin.Telang leaves (Clitoria ternatea L.) contain flavonoid compounds that can act as antioxidants by donating hydrogen so as to stabilize electron deficiency in free radicals. The purpose of this study was to determine the antioxidant activity of telang leaf extract by looking at the IC50 value. Telang leaves were extracted by the maceration method using ethanol solvent.The antioxidant activity test was determined by the DPPH method (1,1-diphenyl-2-picrylhydrazyl) with a vitamin C comparator that has been proven to have a very effective free radical potential. The results showed that the IC50 value of telang leaf extract was 1175 μg / mL, based on this value telang leaf extract is included in the very weak category so that it can be developed as one of the sources antioxidants from natural ingredients.